Propuesta Plan de Marketing para el posicionamiento de la empresa “Casa Cosmética” en el municipio de Obando Valle (2023)
This research aims to design marketing strategies that contribute to the positioning of the Casa Cosmética company in the market, for this the design of a marketing plan that starts from a diagnostic phase on the current situation of the company, an investigation of market that allows to know the ideal client, the competition and the characteristics of the market in which the company operates and thus determine the set of strategies that best adapt to the characteristics of the company and the market segmentation based on the analysis carried out . From the methodological point of view, the research has a descriptive and deductive qualitative-quantitative approach in which interviews and surveys were applied to consumers and employees to collect the data that was later tabulated and analyzed, resulting in a content marketing plan proposal. of a set of strategies to strengthen the positioning of the brand, recognition by the public and a better operational and financial result of the company.